Skills, entrepreneurship and new business models: Ways to rejuvenate the German industrial model - Jörg Bienert; Klaus-Günter Deutsch; Hans-Peter Klös; Klaus-Heiner Röhl (Institut der deutschen Wirtschaft (IW), 2018)
New business models are at the heart of the global competitive challenge. In several areas of manufacturing and closely related services industries, new market participants, business models and technologies lead to faster change in market conditions and the competitive environment. These developments pose new challenges for the successful German industrial system. Strategic treatment of innovation, a stronger focus on disruptive technologies or business models, organ-izational experimentation such as spin-outs to retain entrepreneurial employees, less intra-cor-porate bureaucracy in such ventures and the interaction with new business partners are key elements to master the evolving challenges. Entrepreneurship, new business models and inno-vation in rapidly changing markets should be fostered by focused approaches of management and general economic policies. This includes measures to facilitate to entrepreneurship educa-tion, an entrepreurial culture and corporate training. [...]
Keywords: H25; L53; L60; O32; 330